Analysis of Problems in 996 Defective Hospital Admission Records and Relevant Countermeasures. (May 2014) - Yu, Mingxia; Zhang, Hongwei; Deng, Yiyang; Liu, Yamin
Abstract Objective. To improve the quality of medical records and develop countermeasures by analyzing the problems existing in the hospital admission records of the medical records of inpatients. Methods. To conduct a statistical analysis on 996 cases of defective hospital admission records in the whole year of 2013, according to the Basic Criterion of Documentation of the Medical Record launched by the Ministry of Health and the Writing Quality Checklist of Medical Records (Final) of Inpatients issued by the Beijing Health Bureau, which includes twelve items: general condition, chief complaint, history of present illness, physical examination and so on. Results. Of the defective hospital admission records, the records without the doctor's signature account for 42.37%, the records without the final diagnosis or with an incomplete final diagnosis account for 40.46%, and defects in surgical medical records are significantly more than those of the department of internal medicine. Conclusion. Through the special quality check of hospital admission records, we can identify the basic reasons for the defects in medical records, formulate effective countermeasures and continuously improve the quality of medical records.